Thông lệ quốc tế về sử dụng hợp lý hay quyền được dùng tài liệu có bản quyền tại các thư viện đại học và thư viện chuyên ngành - Tạ, Bá Hưng (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
Mentions basic targets of the Law on intellectual property as well as Copyright law which assure the harmony and balance of benefits between the author and user. Presents 8 popular common practices on fair use or right of using copyrighted materials which can be applied at university and special libraries according to the guidelines of the Association of Research Libraries (USA).